2021
DOI: 10.3389/fmed.2021.656086
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Antagonizes Glucose Fluctuation Induced Renal Injury by Inhibiting Aerobic Glycolysis via HIF-1α/miR-210/ISCU/FeS Pathway

Abstract: Background and Objective: Glucose fluctuation (GF) has been reported to induce renal injury and diabetic nephropathy (DN). However, the mechanism still remains ambiguous. Mitochondrial energy metabolism, especially aerobic glycolysis, has been a hotspot of DN research for decades. The activation of HIF-1α/miR210/ISCU/FeS axis has provided a new explanation for aerobic glycolysis. Our previous studies indicated quercetin as a potential therapeutic drug for DN. This study aims to evaluate levels of aerobic glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Similarly, glucose fluctuations intensified aerobic glycolysis in cultured mouse mesangial cells. Oscillating glucose lowered the activity of aconitase, an enzyme of the Krebs cycle, and suppressed mitochondrial respiratory chain complex I [103]. At the same time, a reduction in the mitochondrial complex I activity was observed in the rat brain in a model of T1D [104].…”
Section: Altered Mitochondrial Homeostasismentioning
confidence: 88%
See 1 more Smart Citation
“…Similarly, glucose fluctuations intensified aerobic glycolysis in cultured mouse mesangial cells. Oscillating glucose lowered the activity of aconitase, an enzyme of the Krebs cycle, and suppressed mitochondrial respiratory chain complex I [103]. At the same time, a reduction in the mitochondrial complex I activity was observed in the rat brain in a model of T1D [104].…”
Section: Altered Mitochondrial Homeostasismentioning
confidence: 88%
“…The metabolic changes and dysfunction of organelles under high-GV conditions ultimately reduce the survival of a number of cells. Some in vitro studies have demonstrated the pro-apoptotic effect of IHG in endothelial cells [25,128,129], mesangial cells [103,130], cardiomyocytes [131], neurons [132,133], glial cells [134], Schwann cells [135] and beta cells [98,136]. The activation of GV-related apoptosis was attributed to mitochondrial dysfunction, ER stress and autophagy [100,124,127,131].…”
Section: Apoptosismentioning
confidence: 99%
“…In comparison to constant high- or low-glucose condition, oscillating levels of blood glucose can induce harder cytotoxicity, such as inflammatory injury, oxidative stress, and apoptosis in the fields of DN development [ 3 , 10 ] and other DM-related complication [ 47 ]. In the present study, we used HEK-293 cell to build a cellular model exposed to different high-glucose circumstances which partly mimic constant and oscillating high-glucose conditions in DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that GF condition had apoptosis-inducing and oxidative stress abilities on cells, including MCs [ 4 ], podocytes [ 5 ], and vascular endothelial cells [ 6 ]. Further, another study presented that GF increased aerobic glycolysis switch and aggravated renal injury, such as reducing cell proliferation and exacerbating inflammation and apoptosis, in a MC cell model [ 10 ]. Our results were in accordance with previous studies, and we testified the GF-related renal injury in HEK-293 cell which further verified the association between GF and DN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation